2018
DOI: 10.1136/bmj.k2167
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and risk of pregnancy related hypertensive disorders: mendelian randomisation study

Abstract: ObjectiveTo use mendelian randomisation to investigate whether 25-hydroxyvitamin D concentration has a causal effect on gestational hypertension or pre-eclampsia.DesignOne and two sample mendelian randomisation analyses.SettingTwo European pregnancy cohorts (Avon Longitudinal Study of Parents and Children, and Generation R Study), and two case-control studies (subgroup nested within the Norwegian Mother and Child Cohort Study, and the UK Genetics of Pre-eclampsia Study).Participants7389 women in a one sample m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
0
35
0
1
Order By: Relevance
“…Several RCTs and meta-analyses of RCTs have been published on vitamin D supplementation during pregnancy and its effect on neonatal and maternal outcomes [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Amongst the many meta-analyses published, we focus on the findings of the most recent ones and/or the ones including the highest number of study participants.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Several RCTs and meta-analyses of RCTs have been published on vitamin D supplementation during pregnancy and its effect on neonatal and maternal outcomes [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Amongst the many meta-analyses published, we focus on the findings of the most recent ones and/or the ones including the highest number of study participants.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Recently, 2 small randomized controlled studies found a beneficial effect of vitamin D supplementation in the incidence of this entity 24,25 . However, a mendelian study with thousands of pregnant women did not find a clear causal effect between preeclampsia or hypertension during pregnancy with vitamin D deficiency 26 . This condition, preeclampsia, which is defined as the existence of de novo hypertension accompanied by proteinuria after 20 weeks' gestation, is associated with vasculitis and inflammation 27 .…”
Section: Lessons From Maternity and New Datamentioning
confidence: 94%
“…There are two studies showing that vitamin D supplementation in pregnancy reduced the risk of PE . In contrast, a recent study suggested that there was no strong evidence supporting a causal effect of vitamin D status on PE . Mirzakhani also reported that vitamin D supplementation (4400 vs 400 IU/d) initiated at 10‐18 gestational weeks of pregnancy did not reduce the risk of PE.…”
Section: Innate Immunitymentioning
confidence: 99%